Music performance anxiety in classical musicians – what we know about what works - Matei, Raluca (BJPsych Int, 2017)
When pursued professionally, the demands of musical training and performance can interfere with musicians’ well-being and health. Music performance anxiety, while energising at optimal levels, impairs performance quality when excessive. A range of interventions has been explored to address it. However, the poor methodological quality of such studies and the complexity of this issue should mobilise further research resources in this direction.